Assessment of the arrival signatures of the March 2012 CME–CME interaction event with respect to Mercury, Venus, Earth, STEREO-B, and Mars locations - Soni, Shirsh Lata; Selvakumaran, R.; Thampi, R. Satheesh (Frontiers in Astronomy and Space Sciences, 2023)
In March 2012, favourable positions of Mercury, Venus, Earth, Mars, and STEREO-B in the inner solar system provided an opportunity to understand the global structure and the propagation of a CME across the inner solar system. On March 7, 2012, the Sun ejected two very fast CMEs from solar active region NOAA AR11489, which were accompanied by two X-class flares. Initialization and subsequent fast expansion from lower coronal heights of flux rope structures were detected as their early eruption signatures in SDO observations. White light observations have been imaged by SOHO/LASCO and followed from 00:24 UT on March 7, 2012. We examined the kinematics of the reported CMEs and found a significant exchange of momentum and kinetic energy during the interaction, indicating that the collision was close to inelastic. Further, we observed the arrival of this merged CME event at different distances in the inner solar system and compared the arrival time with other models. The reported event arrived at Mercury at 04:30 UT, Venus at 13:28 UT on March 7, 2012, and it took roughly 36 hours to reach STEREO-B. The arrivals at Mercury and Venus are observed in the magnetometer measurements onboard Messenger and VEx, respectively. A powerful Interplanetary shock was observed at 1 AU around 34 hours after the two X-class flares and CMEs eruption. Subsequently, a south-directed interplanetary magnetic field (IMF) was observed at Earth, indicating the arrival of an ICME. This event caused the sudden storm commencement and development of one of the major intense geomagnetic storms of SC 24, with a minimum Dst value of -148nT. The observations by the Mars Express (MEX) mission indicated the arrival of a merged CME ~2.5 days after its initial observation at Sun. We have analysed the evolution of these CMEs as well as their propagation in the inner heliosphere and arrival signatures at four planetary locations. The propagation and arrival signatures are compared to simulations using the WSA ENLIL+Cone model and the Drag Based Model at various vantage points.The study showcases the importance of multi-vantage point observations in understanding the propagation of CMEs and their interactions.